Peran Self-Efficacy terhadap Motivasi Menghafal Al-Qur’an pada Remaja Pesantren - Framita, Gusty Syaiim; Salsabila, Mustamira Sofa; Putra, Andi Eka (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Self-efficacy is an individual's belief in his or her ability to complete a particular task. In the context of memorizing the Qur'an, students often face various obstacles such as time constraints, difficulty remembering, losing memorization, laziness, and lack of confidence. This study aims to determine the relationship between self-efficacy and motivation to memorize the Qur'an in grade X and XI students of Madrasah Aliyah at Darul Huffaz Islamic Boarding School Lampung, as many as 55 respondents. The method used is quantitative correlation with total sampling technique. Data collection using two scales, namely the self-efficacy scale (15 items, α = 0.830) and the motivation scale to memorize the Qur'an (22 items, α = 0.856). Data analysis was carried out using the help of SPSS 21.0. The results showed a significant positive relationship between self-efficacy and motivation to memorize the Qur'an with a coefficient value of r = 0.331 and p = 0.000 (p 0.05), and an effective contribution of 57.5%. It can be concluded that the higher the self-efficacy, the higher the motivation of students in memorizing the Qur'an, and vice versa.